Über Geometrie der Mannigfaltigkeit der ausartigen ebenen Kurven dritter Ordnung im projektiven Raume P3 - Pekarskienė, A. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Ю. Пекарскене. О геометрии многообразия выражденных плоских кривых третьего порядка в P3A. Pekarskienė. Išsigimusių plokščių trečios eilės kreivių daugdaros erdvėje P3 geometrijos klausimu